2021
DOI: 10.1016/j.ijrefrig.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the novel home freezing system on microstructure, color, antioxidant activity, and microbiological properties of strawberries

Abstract: Highlights Novel home freezing provides quick freezing at 1.51 cm h − 1 for strawberry. Strawberries reached -15°C approximately 234 minutes shorter in the novel system. Color was protected better after quick freezing during 4 month storage. Antioxidant activity of the strawberries increased 8.96% after the novel freezing. Fruits and vegetables can be frozen quickly at home by this no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…There are several methods to measure the freezing time, as mentioned by Ramaswamy and Marcotte (2005). One of them is the procedure applied by Rayman Ergün et al (2021) who considers the freezing time as the time taken to reach a temperature of −15°C from 0°C at the cold point. Taking into account this definition, in our experiment the freezing rate was .176 mm·min −1 (2.93 μm·s −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are several methods to measure the freezing time, as mentioned by Ramaswamy and Marcotte (2005). One of them is the procedure applied by Rayman Ergün et al (2021) who considers the freezing time as the time taken to reach a temperature of −15°C from 0°C at the cold point. Taking into account this definition, in our experiment the freezing rate was .176 mm·min −1 (2.93 μm·s −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Ergün et al. (2021) reported that subjecting strawberries to quick freezing resulted not only in a shorter freezing time and higher freezing rate (1.51°cm/h) than static freezing but also had positive effects on the color, tissue structure, and antioxidant activity of the samples. The mean equivalent diameters of the ice crystals in apples were reported to be 71, 55, and 45 µm for slow (2°C/min), intermediate (12.6°C/min), and fast (18.5°C/min) freezing, respectively (Vicent et al., 2017).…”
Section: Freezing Process In Fruits and Vegetablesmentioning
confidence: 99%
“…A study by Redmond et al (2002) explored the effects of different freezing conditions on potato freezing, and found that rapid freezing can reduce drip loss as well as making the product softer, but at the same time VC is retained to a greater extent with little difference in taste compared to the fresh samples (Redmond et al, 2002). Rayman Ergün et al (2021) reported that the higher freezing rate offers better prospects for the preservation of the tissue structure and cell wall, the antioxidant activity of the strawberries is retained to a greater extent after rapid freezing, and the brightness and redness of the fruit is better preserved during storage in the fast-frozen samples. (Rayman Ergün et al, 2021).…”
Section: Control Of the Freezing Ratementioning
confidence: 99%
“…Rayman Ergün et al (2021) reported that the higher freezing rate offers better prospects for the preservation of the tissue structure and cell wall, the antioxidant activity of the strawberries is retained to a greater extent after rapid freezing, and the brightness and redness of the fruit is better preserved during storage in the fast-frozen samples. (Rayman Ergün et al, 2021). Xu et al (2014) discovered that drip loss from high-pressure carbon infusion (HPCI), liquid nitrogen and ultra-low temperature freezing (ULTF) as methods used to preserve frozen carrot slices were 8.29, 12.36 and 12.45%, respectively.…”
Section: Control Of the Freezing Ratementioning
confidence: 99%